RNA-Binding Proteins Driving the Regulatory Activity of Small Non-coding RNAs in Bacteria - Quendera, Ana P.; Seixas, André F.; dos Santos, Ricardo F.; Santos, Inês; Silva, João P. N.; Arraiano, Cecília M.; Andrade, José M. (Frontiers in Molecular Biosciences, 2020)
Small non-coding RNAs (sRNAs) are critical post-transcriptional regulators of gene expression. Distinct RNA-binding proteins (RBPs) influence the processing, stability and activity of bacterial small RNAs. The vast majority of bacterial sRNAs interact with mRNA targets, affecting mRNA stability and/or its translation rate. The assistance of RNA-binding proteins facilitates and brings accuracy to sRNA-mRNA basepairing and the RNA chaperones Hfq and ProQ are now recognised as the most prominent RNA matchmakers in bacteria. These RBPs exhibit distinct high affinity RNA-binding surfaces, promoting RNA strand interaction between a trans-encoding sRNA and its mRNA target. Nevertheless, some organisms lack ProQ and/or Hfq homologs, suggesting the existence of other RBPs involved in sRNA function. Along this line of thought, the global regulator CsrA was recently shown to facilitate the access of an sRNA to its target mRNA and may represent an additional factor involved in sRNA function. Ribonucleases (RNases) can be considered a class of RNA-binding proteins with nucleolytic activity that are responsible for RNA maturation and/or degradation. Presently RNase E, RNase III and PNPase appear to be the main players not only in sRNA turnover but also in sRNA processing. Here we review the current knowledge on the most important bacterial RNA-binding proteins affecting sRNA activity and sRNA-mediated networks.